IMPLEMENTASI MANAJEMEN PENDIDIKAN SEKOLAH DASAR NEGRI 1 SIDODADI - Dirta Putri Margiati; Nicky Dwi Puspaningtyas (Journal of Arts and Education, 2021)
Education is an activity that is required to initiate, facilitate and increase the seriousness and quality of learning in students. This research is a qualitative descriptive research. The method of collection is done by interview method. This study aims to describe and analyze Curriculum Management, Student Management, Educator Management and Education Personnel. And the results of this study are Curriculum Management at SDN 1 Sidodadi, Management of students who have been going well and Management of Educators and Education Personnel that have been carried out in accordance with the function of education management.